Metadherin Regulation of Vascular Endothelial Growth Factor Expression Is Dependent Upon the PI3K/Akt Pathway in Squamous Cell Carcinoma of the Head and Neck. Issue 6 (February 2015) - Zhu, Gang-cai; Yu, Chang-yun; She, Li; Tan, Hao-lei; Li, Guo; Ren, Su-ling; Su, Zhong-wu; Wei, Ming; Huang, Dong-hai; Tian, Yong-quan; Su, Ri-na; Liu, Yong; et al.
Abstract : Abstract: Our previous study indicated overexpression of metadherin (MTDH) is an adverse prognostic factor in squamous cell carcinoma of the head and neck (SCCHN) and promotes SCCHN cell proliferation and invasion. However, its mechanism remains unclear. Recent studies have indicated that MTDH is a cancer-metastasis-associated molecule that participates in the process of angiogenesis. Therefore, the study is aimed to investigate that whether vascular endothelial growth factor (VEGF), as one of the most potent proangiogenic cytokines, is regulated by MTDH and the role of the phosphatidylinositide 3-kinases/Protein Kinase B (PI3K/Akt) pathway in this process of regulation and the clinical significance of both MTDH and VEGF in SCCHN. Immunohistochemistry was used to assay the expression of MTDH and VEGF in a cohort of 189 SCCHN patients with intact follow-up information. The expression of MTDH was then upregulated or inhibited by lentivirus-mediated MTDH Complementary deoxyribonucleic acid or MTDH short hairpin ribonucleic acid (shRNA) to observe the resulting alterations in VEGF expression and the PI3K/Akt signaling pathway in SCCHN cell lines. In addition, the PI3K/Akt pathway was modulated to observe the resulting changes in the MTDH-mediated expression of VEGF. The immunohistochemistry data showed that MTDH expression is positively correlated with VEGF expression in SCCHN tissues. Moreover, the overexpression of MTDH in SCCHN Tu686 and 5-8F cells led to increases in the expression of VEGF, and this effect was accompanied by activation of the PI3K/Akt pathway. Conversely, shRNA-mediated knockdown of MTDH led to decreased VEGF expression. In addition, inhibition of the Akt signaling pathway reversed the upregulation of VEGF resulting from MTDH overexpression. Moreover, the survival analysis revealed that VEGF is an independent prognostic factor, and a combined survival analysis based on both MTDH and VEGF showed synergistic effects in the prognosis evaluation of SCCHN patients. The findings of the present study demonstrate that MTDH regulates the expression of VEGF via the PI3K/Akt signaling pathway, indicating the potential role of the MTDH-mediated activation of VEGF signaling pathway in SCCHN angiogenesis and metastasis. Abstract : Supplemental Digital Content is available in the text